Model and method of automated high-precision measurement of three-dimensional objects based on computed tomography data - Vakulik, Eugen; Smelyakov, Kyrylo; Chupryna, Anastasiya (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2026)
The subject of study is the linear dimensions of three-dimensional objects based on computed tomography data, specifically metallic foreign bodies in human tissues and organs. The purpose of the study is to develop a mathematical model and a method for automated, high-precision measurement of the linear dimensions of three-dimensional objects based on computed tomography results, with implementation in the form of software. Objectives: to formulate a mathematical model for representing a three-dimensional object in voxel space; to develop a method for segmenting metal fragments based on computed tomography results; to propose a method for spatial alignment of segmented objects based on principal component analysis; develop a method for determining the maximum linear dimension of an object in a new coordinate system; implement the proposed model and method as software and experimentally verify the measurement accuracy. Research methods: analysis of tomographic parameters, threshold segmentation with adaptive selection of threshold values, wave-based algorithm for finding connected components, principal component analysis to determine the object’s orientation, voxel modeling, and calculation of Euclidean distances between boundary points of a three-dimensional object. Results. A mathematical model for representing a three-dimensional object and a method for automated high-precision determination of its maximum linear dimension are proposed. The method was implemented as a software module and tested on 72 samples of metal fragments of six types embedded in the biological tissues of pig organs. The average deviation does not exceed 3%, and in the most complex cases remains within 5%, which indicates the high accuracy and stability of the proposed approach. Conclusions: The developed model and method ensure automated and objective determination of the linear dimensions of foreign bodies based on computed tomography data without operator intervention. The proposed software can be used in military medicine, forensic medical examination, disaster medicine, and healthcare facilities where the speed and reliability of diagnostic decisions are critically important.